Archeological Survey within the Chickasaw National Recreation Area, Murray County, Oklahoma - Osborn, Alan J.; Hartley, Ralph J. (the Digital Archaeological Record)
The Midwest Archeological Center (MWAC), National Park Service in Lincoln, Nebraska was contacted by the staff of the Chickasaw National Recreation Area in Sulphur, Oklahoma to request assistance in the completion of an archeological survey of areas that would be impacted by future renovations, rehabilitations, and upgrades of facilities within Chickasaw NRA. These projects include: 1) installation and/or replacement of twenty-two 18’ steel culverts along back country roads; 2) the installation of thirteen vault toilets; 3) rehabilitation of the comfort station near Buffalo Springs; 4) installation of a electrical conduit and solar panel at Antelope Springs; 5) upgrade of roads and modification of picnic areas within the Platt Historic District; 6) rehabilitation of berms and drainage features at Pavilion Springs; and, 7) renovation of eroded portions of Rock Creek multi-use Trail No.1. Archeologists from MWAC carried out the survey and monitoring associated with these projects between June 23-29, 2008. This report provides a description of the project area and location; pertinent background information; the nature of the proposed renovation and rehabilitation projects; and the results of the archeological survey(s) and auger tests conducted within Chickasaw NRA.